1997
DOI: 10.1115/1.2833498
|View full text |Cite
|
Sign up to set email alerts
|

Point Contact EHL Based on Optically Measured Three-Dimensional Rough Surfaces

Abstract: This paper presents a numerical solution for the elastohydrodynamic lubrication in point contacts, using optically measured three-dimensional rough surface profiles as input data. The multi-grid computer program originally developed by Ai and Cheng (1993, 1994) is modified, so that both contacting surfaces can be three-dimensional measured rough surfaces moving at different velocities. Many different engineering surfaces are measured and analyzed in the present study, demonstrating that the numerical analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 25 publications
1
44
0
3
Order By: Relevance
“…For more details about how the surface roughness of honed gears is incorporated in the EHL model, please refer to Zhu and Ai, 28 Zhu et al, 29 etc. The initial estimate of elastic deformation is obtained with the original distributed pressure.…”
Section: Numerical Calculationmentioning
confidence: 99%
“…For more details about how the surface roughness of honed gears is incorporated in the EHL model, please refer to Zhu and Ai, 28 Zhu et al, 29 etc. The initial estimate of elastic deformation is obtained with the original distributed pressure.…”
Section: Numerical Calculationmentioning
confidence: 99%
“…The amplitude, A, is 0.4 µm for the transversal and longitudinal waves, but 0.2 µm for the isotropic one, while the wavelengths ω x and ω y in the following expressions are all 0.5a. The operating conditions used are summarized in Table 3 δ(x, y) A cos(2πx/ω x ) (12) δ(x, y) A cos(2πy/ω y )…”
Section: Sinusoidal Wavinessmentioning
confidence: 99%
“…Many full numerical solutions to line and point contact elastohydrodynamic lubrication (EHL) problems have been developed in the past, which include those by Dowson and Higginson [1], Ranger et al [2], Hamrock and Dowson [3], Oh and Rohde [4], Evans and Snidle [5], Okamura [6], Zhu and Wen [7], Lubrecht [8], Venner [9], Ai [10], Xu and Sadeghi [11], Zhu and Ai [12], and others. Great efforts have been made to significantly improve the solution convergence speed and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Chang and Zhao [13] continued to study the differences between Newtonian and non-Newtonian lubricant models in transient micro-EHL and showed that the non-Newtonian effect was significant, particularly with roughness of relatively short wavelength. A study of micro-EHL under point contact conditions using measured roughness was carried out by Xu and Sadeghi [14] and Zhu and Ai [15]. In these studies, however, the amplitude of the roughness was relatively small compared to the thickness of the films generated.…”
Section: Dowson and Higginson (1959)mentioning
confidence: 99%